Melanocortin receptor agonists in the treatment of male and female sexual dysfunctions: results from basic research and clinical studies. (November 2014) - Ückert, Stefan; Bannowsky, Andreas; Albrecht, Knut; Kuczyk, Markus A
<x xml:space="preserve">Abstract</x> Introduction: Over the last 20 years, basic and clinical research activities studying the male and female sexual responses have led to several pharmacological options to treat male erectile dysfunction (ED) and female arousal and orgasmic disorders. While some strategies exclusively focus on peripheral mechanisms – such as nitric oxide/cyclic GMP signaling, which is known to play a role in the control of genital vascular and nonvascular smooth muscle – others have considered the central pathways involved in mediating arousal and orgasmic functions in females as well as the induction of penile erection in males. Aside from dopaminergic agonists, drugs known to target the central melanocortin system have also been assumed to have a promising potential in the treatment of female and male sexual dysfunctions. Areas covered: The present review summarizes the achievements that have been made in the clinical development of melanocortin receptor (MCR) agonists (melanotan I, melanotan II, bremelanotide) for the treatment of symptoms of sexual arousal and orgasmic disorders in adult females and ED in males. Expert opinion: The data available at present have facilitated our understanding of how the melanocortin pathway regulates both the male and female sexual functions. Indeed the data warrant further investigation to demonstrate the impact of the activation of MCRs by specific agonists on penile erection and female arousal and orgasm function.